Interdisciplinary Diagnosis, Therapy and Follow-up of Patients with Endometrial Cancer. Guideline (S3-Level, AWMF Registry Number 032/034-OL, April 2018) – Part 2 with Recommendations on the Therapy and Follow-up of Endometrial Cancer, Palliative Care, Psycho-oncological/Psychosocial Care/Rehabilitation/Patient Information and Healthcare Facilities - Emons, Günter; Steiner, Eric; Vordermark, Dirk; Uleer, Christoph; Bock, Nina; Paradies, Kerstin; Ortmann, Olaf; Aretz, Stefan; Mallmann, Peter; Kurzeder, Christian; Hagen, Volker; van Oorschot, Birgitt; Höcht, Stefan; Feyer, Petra; Egerer, Gerlinde; Friedrich, Michael; Cremer, Wolfgang; Prott, Franz-Josef; Horn, Lars-Christian; Prömpeler, Heinrich; Langrehr, Jan; Leinung, Steffen; Beckmann, Matthias W.; Kimmig, Rainer; Letsch, Anne; Reinhardt, Michael; Alt-Epping, Bernd; Kiesel, Ludwig; Menke, Jan; Gebhardt, Marion; Steinke-Lange, Verena; Rahner, Nils; Lichtenegger, Werner; Zeimet, Alain; Hanf, Volker; Weis, Joachim; Mueller, Michael; Henscher, Ulla; Schmutzler, Rita K.; Meindl, Alfons; Hilpert, Felix; Panke, Joan Elisabeth; Strnad, Vratislav; Niehues, Christiane; Dauelsberg, Timm; Niehoff, Peter; Mayr, Doris; Grab, Dieter; Kreißl, Michael; Witteler, Ralf; Schorsch, Annemarie; Mustea, Alexander; Petru, Edgar; Hübner, Jutta; Rose, Anne Derke; Wight, Edward; Tholen, Reina; Bauerschmitz, Gerd J.; Fleisch, Markus; Juhasz-Boess, Ingolf; Lax, Sigurd; Runnebaum, Ingo; Tempfer, Clemens; Nothacker, Monika J.; Blödt, Susanne; Follmann, Markus; Langer, Thomas; Raatz, Heike; Wesselmann, Simone; Erdogan, Saskia (Geburtshilfe und Frauenheilkunde, 2018)
Summary The first German interdisciplinary S3-guideline on the diagnosis, therapy and follow-up of patients with endometrial cancer was published in April 2018. Funded by German Cancer Aid as part of an Oncology Guidelines Program, the lead coordinators of the guideline were the German Society of Gynecology and Obstetrics (DGGG) and the Gynecological Oncology Working Group (AGO) of the German Cancer Society (DKG).Purpose Using evidence-based, risk-adapted therapy to treat low-risk women with endometrial cancer avoids unnecessarily radical surgery and non-useful adjuvant radiotherapy and/or chemotherapy. This can significantly reduce therapy-induced morbidity and improve the patientʼs quality of life as well as avoiding unnecessary costs. For women with endometrial cancer and a high risk of recurrence, the guideline defines the optimal extent of surgical radicality together with the appropriate chemotherapy and/or adjuvant radiotherapy if required. An evidence-based optimal use of different therapeutic modalities should improve the survival rates and quality of life of these patients. This S3-guideline on endometrial cancer is intended as a basis for certified gynecological cancer centers. The aim is that the quality indicators established in this guideline will be incorporated in the certification processes of these centers.Methods The guideline was compiled in accordance with the requirements for S3-level guidelines. This includes, in the first instance, the adaptation of source guidelines selected using the DELBI instrument for appraising guidelines. Other consulted sources included reviews of evidence, which were compiled from literature selected during systematic searches of literature databases using the PICO scheme. In addition, an external biostatistics institute was commissioned to carry out a systematic search and assessment of the literature for one part of the guideline. Identified materials were used by the interdisciplinary working groups to develop suggestions for Recommendations and Statements, which were then subsequently modified during structured consensus conferences and/or additionally amended online using the DELPHI method, with consent between members achieved online. The guideline report is freely available online.Recommendations Part 2 of this short version of the guideline presents recommendations for the therapy of endometrial cancer including precancers and early endometrial cancer as well as recommendations on palliative medicine, psycho-oncology, rehabilitation, patient information and healthcare facilities to treat endometrial cancer. The management of precancers of early endometrial precancerous conditions including fertility-preserving strategies is presented. The concept used for surgical primary therapy of endometrial cancer is described. Radiotherapy and adjuvant medical therapy to treat endometrial cancer and uterine carcinosarcomas are described. Recommendations are given for the follow-up care of endometrial cancer, recurrence and metastasis. Palliative medicine, psycho-oncology including psychosocial care, and patient information and rehabilitation are presented. Finally, the care algorithm and quality assurance steps for the diagnosis, therapy and follow-up of patients with endometrial cancer are outlined.
Keywords: endometrial cancer; guideline; precancers; therapy; follow up